Indirectness as A Communication Style of Javanese Women in Making Offers in Public Spaces - Megah, Suswanto Ismadi; Jaffar, Jawakhir Mior (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
Language usage patterns are a reflection of society and gender-based social divisions. In the modern era, the situation of woman language will differ due to the social situation. The effects of modernity and globalization, which are ever more prevalent, are felt in many facets of human existence and become more apparent over time particularly when it relates to cultural and linguistic shifts in gendered communication. This study aims to uncover how Javanese women communicate in offering their 'services' in public areas. This study highlights how commercial sex workers offer their services near Surabaya City. Data obtained from real communication when the subjects who have been offering their service. What language style applied from five subjects. This study concludes that the Javanese women speakers applied the Javanese language to different levels. While the use of Indonesian language in their communication as an alternative language for Javanese speakers to choose words or phrases in order to prevent language speech level misuse and speakers' inability to use the proper Javanese stylistic level, particularly when speaking to younger subjects. These findings emphasize the need for further exploration of the cultural and linguistic dynamics in Javanese society, particularly in professions that involve nuanced communication. This study also opens pathways for future research into the sociological and linguistic dimensions of language use in other sensitive or stigmatized professions, broadening the scope of inquiry within social humanities.